Upaya Guru dalam Menegakkan Kedisiplinan Siswa di Madrasah Ibtidaiyah Negeri 2 Sarolangun - Umar Dhani; Prapti Octavia Ningsih (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This research is motivated by the lack of student discipline in implementing regulations at Madrasah Ibtidaiyah Negeri 2 Sarolangun. The purpose of this study is to describe the efforts made by teachers in disciplining students at Madrasah Ibtidaiyah Negeri 2 Sarolangun. The number of informants was 29 people, namely the principal, six teachers, ten students and five parents of students. The data used are primary data and secondary data. The data collection techniques used are non-participant observation, in-depth interviews and document studies. Then the unit of analysis is the group. The data analysis technique used is interactive data analysis (Miles and Huberman). Namely data collection, data reduction, data presentation, and drawing conclusions. The results of this study are; (First) Teachers Provide Good Role Models for Students. (Second) The tolerance shown by teachers to students who arrive late, (Third) Teachers provide valuable advice to noisy students, (Fourth) Teachers are polite in their speech, such as telling stories about the prophets and apostles (Fifth) Teachers teach social attitudes, such as loving, respecting, and appreciating each other, (Sixth) Teachers provide rewards and punishments to students, and (Seventh) There is good cooperation between teachers and parents of students, such as parents asking teachers about their children's behavior at Madrasah Ibtidaiyah Negeri 2 Sarolangun.